The Performance of Bamboo Fibre as Reinforcement Concrete in Substitude Cement with Nano Silica in Terms of Workability, Compressive Strength and Tensile Strength - HAZIQ, MUHAMMAD; Mohd Sufyan Abdullah (Progress in Engineering Application and Technology, 2024)
In construction, concrete is a crucial material valued for its affordability, robustness, heat and fire resistance, wide availability, endurance, and versatility. However, its limited tensile strength restricts its use in areas dominated by tensile forces. Bamboo offers a compelling alternative: it is abundant in fibres, naturally sourced, cost-effective, easily procurable, and notably strong in both tension and compression. To explore the mechanical properties of bamboo fibre as reinforcement in concrete with nano silica as a cement substitute, laboratory investigations were conducted on workability, compressive strength, and split tensile strength. Based on these observations, conclusions were drawn about the impact of adding bamboo fibre and nano-silica to concrete. In summary, bamboo fibres and nano-silica are promising materials that can enhance concrete's strength, ductility, and post-cracking load-carrying capacity. Furthermore, a comparison of compressive strength test results for cube samples at 7 days and 28 days was made, as well as a split tensile strength test for a cylinder sample at 28 days. For both the 7 days and 28 days compressive strength tests, sample 4 (fibre 0.20%, nano-silica 2.0%) showed the highest strength, and for the split tensile strength test, sample 4 was also the highest. Additionally, the fibres allowed the concrete to sustain higher loads than ordinary concrete while reducing fracture width and deflection. Consequently, specimens with varying fibre contents showed considerable improvement in tensile strength as the fibre volume percentage increased.